Migration, Gender and Social Justice: Perspectives on Human Insecurity - Truong, Tanh-Dam (Hexagon Series on Human and Environmental Security and Peace, 2014)
Gender Studies; Migration; International Humanitarian Law, Law of Armed Conflict; Human Rights; Anthropology; Public Law